Observation of Primary and Secondary Enhancement of Emission Spectra From Spatially Confined Laser-Induced Aluminum Plasmas - Boping Xu (IEEE Photonics Journal, 2022)
In this study, four cylindrical cavities with diameters of more than 10 mm are utilized to confine aluminum plasmas to improve the signal intensities of laser-induced breakdown spectroscopy (LIBS). Primary and secondary enhancements of spectra are observed. This phenomenon is attributed to the fact that plasmas are compressed into a smaller core area with denser population of excited atoms by reflected shockwaves more than one time. The delay time for both primary and secondary signal enhancements is postponed with decreasing the laser energy or increasing the cavity diameter. Relative standard deviations (RSDs) of spectra signal in different experimental conditions are discussed to illustrate the uncertainties of measurement. In addition, enhancement factor, signal-to-background ratio (SBR) and signal-to-noise ratio (SNR) are also examined in the two cases. The fast images of plasma plume further prove the enhancements of emission intensity, as well as its RSD.